Green Corrosion Inhibitor of Mild Steel in Hydrochloric Acid by the Extract of Native Plant Stevia rebaudiana Leaves - Cang, Hui; Shi, Wenyan; Lu, Yu; Shao, Jingling; Xu, Qi (Asian Journal of Chemistry, 2012)
The inhibition of the corrosion of mild steel in hydrochloric acid solution by the extract of Stevia rebaudiana leaves has been studied using weight loss, electrochemical impedance spectroscopy and potentiodynamic polarization techniques. Inhibition was found to increase with increasing concentration of the leaves extract. The effect of temperature, immersion time and acid concentration on the corrosion behaviour of mild steel in 1M HCl with addition of extract was also studied. The inhibition was assumed to occur via adsorption of the inhibitor molecules on the metal surface. The adsorption of the extract on the mild steel surface obeys the Temkin adsorption isotherm. The activation energy as well as other thermodynamic parameters (Ea, DH and DS) for the inhibition process was calculated. These thermodynamic parameters show strong interaction between inhibitor and mild steel surface. The results obtained show that the extract of the leaves of Stevia rebaudiana could serve as an effective inhibitor of the corrosion of mild steel in hydrochloric acid media.